Preparasi dan Karakterisasi Mikrokristalin Selulosa dari Limbah Serbuk Kayu Penggergajian - Gusrianto, Putra; Zulharmita, Zulharmita; Rivai, Harrizul (Fakultas Farmasi Universitas Andalas, 2011)
A study on the preparation and characterization of microcrystalline cellulose from waste of sawdust has been carried out. A total of 300 grams of sawdust made into alpha-cellulose by multistage pulping method and hydrolyzed by using hydrochloric acid to produce microcrystalline cellulose, which was characterized further. Microcrystalline cellulose obtained as much as 99 grams with a yield of 33%. The organoleptic characteristics were fine powder, white, odorless, and tasteless. Identification with a solution of iodinated zinc chloride produced a blue violet and the infrared spectrum produced nearly the same wavenumber with Vivacel PH 102Â®. Solubility in water was 0.117% and the pH was 5.08, dissolved in a solution of ammonia-copper tetramin. The loss on drying was 5.85 %, the bulk density was 0.329 g/ml and tapped density was 0.542 g/ml. Carrs index value was 39.60%, Hausner ratio was 1.656 and Hydration capacity was 3.191. There was no starch on this microcrystalline cellulose. Microcrystalline cellulose from waste of sawdust generally met the pharmacopoeia requirements and the characteristics were not significantly different from Vivacel PH 102Â®.